Analysing financial globalisation : cross-border investment, international risk sharing, and financial reforms - Schmitz, Martin (Trinity College (Dublin, Ireland). Department of Economics, 2011)
The research topic of this thesis lies in the area of international macroeconomics. In particular, key aspects of financial globalisation are analysed empirically. In the first essay, analysis of 21 industrial countries shows evidence for pro-cyclicality of capital gains on domestic stock markets over a medium term horizon. Thus, with crossborder ownership of portfolio equity investments, potential for hedging against domestic output fluctuations by means of the capital gains channel of foreign liabilities is found. The individual country analysis reveals substantial heterogeneity of these cyclicality patterns. The analysis suggests that this cross-country variation can be explained by the level of economic development and the size of financial markets.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.